Physiological and sport-specific comparison between division I and division II italian male field hockey players - Bartolomei, S.; Nigro, F.; Gubellini, L.; Giacci, S.; Merni, F.; Treno, F.; Cortesi, M.; Semprini, G. (The Journal of Strength and Conditioning Research, 2019)
The purpose of this study was to compare the anthropometric and performance profiles of Division I (D1) and Division II (D2) Italian field hockey players. Fifteen DI players and 15 D2 players (age = 25.4 ± 5.2 years; body mass = 78.5 ± 9.0 kg; and body height = 179.6 ± 7.8 cm) were assessed on one occasion for anthropometry, body composition, physiological measurements, and sport-specific skills. Differences between the 2 groups were evaluated using a 1-way analysis of variance. Pearson correlations were used to examine relationships between the different measurements. Significantly (p = 0.039) lower percentages of body fat were found on D1 group compared with D2 group (-3.5%). A significant difference between the groups were noted for shooting accuracy (p = 0.013), with the D1 group performing 14.5% better than the DII group. No significant differences between the groups were found for shooting speed (p = 0.103) and slalom and dribbling performances (p = 0.292 and p = 0.416, respectively). Physiological assessments did not show any significant differences between the groups. Large correlations (r = 0.73; p < 0.001) were found between shooting speed and accuracy. Moderate correlations were observed between the shooting speed and the hand grip strength, in particular of the left hand (r = 0.61; p = 0.007). Results of this study indicate that the difference between D1 and D2 players may be more related to technical factors than to physical fitness. Ball control, however, may not be a limiting factor in D2 players.